A double layer oral film loaded with doxepin hydrochloride for the treatment of chemotherapy-induced oral mucositis - Wang, Peiyan; Wang, Tianlu; Zhang, Hui; Sun, Pei; Yuan, Changqing; Guo, Yiqing; Liu, Zhaochen; Jiao, Mengyu; Chi, Jingwen; Wang, Kexin; Deng, Jing; Yu, Xiaofei (Frontiers in Pharmacology, 2025)
Chemotherapy-induced oral mucositis is a common complication in cancer therapy. Multiple studies demonstrate that doxepin mouthwash is effective in controlling CIOM pain, while research on its ulcer healing effects and underlying mechanisms remains limited. Additionally, local adhesive formulations of doxepin for oral application are still lacking. In this study, we developed a bilayer oral patch using 3D-printing technology for the localized sustained release of doxepin hydrochloride. This patch demonstrated favorable characteristics, including thinness, flexibility, and excellent mucosal adhesion, while promoting ulcer healing in CIOM animal models. Further investigation revealed that the healing mechanism involves the alleviation of oxidative stress and attenuation of excessive inflammatory responses. The doxepin hydrochloride patch developed in this study provides a novel pharmaceutical option for clinical management of CIOM.